NILAI NORMAL GELOMBANG F DI RSUPN CIPTO MANGUNKUSUMO JAKARTA - Aida Fithrie, Manfaluthy Hakim, Fitri Octaviana, Ahmad Yanuar Safri (Neurona Majalah Kedokteran Neuro Sains, 2012)
BACKGROUND F WAVE IS ONE OF MEASUREMENT FOR DIAGNOSING POLYNEUROPATHY AND PROXIMAL NERVE LESION UNTIL RECENTLY NORMAL VALUE OF F WAVE ARE DIFFERENT AMONG CENTERS THIS STUDY WAS PERFORMED TO CREATE A NORMATIVE DATABASE FOR MEDIAN ULNAR PERONEAL AND TIBIAL NERVES F WAVE RESPONSE OF INDONESIAN PEOPLE AND CAN BE USED AS NORMAL VALUE